Living Actively for Good Health: Older Adults - Jennifer Hillan; Anne Kendall (EDIS)
If you think physical activity is limited to strenuous activities like exercise classes and sports, think again! Read this revised 2-page fact sheet to learn why physical activity is important and how you can get started. Written by Jennifer Hillan and Anne Kendall and published by the UF Department of Family Youth and Community Sciences, October 2010.